2014
DOI: 10.1002/adem.201400067
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Ceramics by Gelation–Freezing Route Using Gelatin

Abstract: This paper reviews an advanced methodology for macroporous ceramic components, that can create nearly honeycomb shaped pore channels, unlike either ellipsoidal or dendritic or lamellar structures obtained via conventional freeze casting. Three main technological features have been discussed in terms of (i) honeycomb shaped morphologies, (ii) relationship between carefully selected freezing conditions, and cell properties generated, (iii) the engineering applications. This simple, ecofriendly, and versatile app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 148 publications
(255 reference statements)
0
33
0
Order By: Relevance
“…On the other hand, the result was attribute to the amount and size of the cracks between the aggregates and matrixes. Ohji et al 17) reported that the compressive strength was associated with the pore morphologies. The strength of the cellular morphologies was higher than that of the lamellar, because the pore size of the cellular structures was much smaller than that of the lamellar.…”
Section: )mentioning
confidence: 99%
“…On the other hand, the result was attribute to the amount and size of the cracks between the aggregates and matrixes. Ohji et al 17) reported that the compressive strength was associated with the pore morphologies. The strength of the cellular morphologies was higher than that of the lamellar, because the pore size of the cellular structures was much smaller than that of the lamellar.…”
Section: )mentioning
confidence: 99%
“…Although a few review papers [16] have been published, they mostly focus on the underlying principles. Little can be found on the range of properties that could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The gelatin-gelation-freezing route has been reported to produce macroporous ceramics with honeycomb-like and non-dendritic pore structures (Fukushima et al 2014). The rational of using gelatin as a binder in the titanium alloy slurries is to alleviate the sedimentation problem of coarse and dense titanium alloy particles during the freeze casting process, with the physically crosslinked gelatin able to hold the particles from fast sedimentation.…”
Section: Introductionmentioning
confidence: 99%